Criminal Actions Of Illegal Logging In The Perspective Of Forestry Law - Wibawa, G.M. Angga Satrya; Muhibbin, Moh.; Parmono, Budi (Scholar Center, 2023)
This research aims to describe the regulation of illegal logging in Indonesian positive law and to analyze how illegal logging is in the perspective of Indonesian criminal law. It is a normative legal research, which examines laws and regulations in a coherent legal system with the values ??contained in the Forestry Law Number 19 of 2004 and Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction, The research results show that illegal logging is regulated in the Forestry Law, namely Forestry Law No. 19 of 2004, changes to Law no. 41 of 1999 became a Law as an instrument in tackling illegal logging crimes. Then Regulation of the Minister of Forestry Number: P.30/Menhut-II/2012 concerning Administration of Forest Products originating from Private Forests. The government also enacted Law no. 18 of 2013 concerning Prevention and Eradication of Forest Destruction as statutory regulations, and is the implementation of Law no. 14 of 1999. Illegal logging sanctions are emphasized in the Forestry Law in the form of criminal sanctions given to those who carry out illegal logging, according to Law no. 18 of 2013 with a maximum prison sentence of 15 years and a maximum fine of IDR 100 billion.